Legal Protection for Consumers Against Hazardous Skincare Products - Wiyardhani, Laras; Wibriansyah, Akbar; Payuti, Yuyut (Research Horizon, 2025)
The proliferation of unregistered skincare products in Indonesia presents a critical legal issue concerning consumer safety and regulatory enforcement. Despite the presence of Law Number 8 of 1999 on Consumer Protection, the circulation of unauthorized cosmetics continues to endanger public health and disrupt market order, as evidenced by national agency of drug and food control 2024 data reporting over 1,000 confiscated illegal products valued in the tens of billions of rupiah. This research addresses the legal question of how effectively current consumer protection laws safeguard individuals from the risks posed by illegal skincare products. The study aims to analyze the normative foundation of consumer protection, evaluate enforcement challenges, and propose strategies to enhance regulatory efficacy. Using a normative juridical method, the research relies on statutory analysis, case studies, and conceptual interpretation based on primary, secondary, and tertiary legal sources. The findings reveal that although the legal framework is normatively adequate, its implementation is hindered by low public awareness, limited digital oversight, and fragmented institutional coordination. The study concludes by recommending integrated digital supervision, strengthened inter-agency collaboration, and continuous consumer legal education as essential measures to reinforce legal protection and curb the spread of unauthorized skincare products in Indonesia.